Design optimization and operating pressure effects in the separation of acetonitrile/methanol/water mixture by ternary extractive distillation. (1st May 2019) - Wang, Yinglong; Bu, Guangle; Geng, Xueli; Zhu, Zhaoyou; Cui, Peizhe; Liao, Zuwei
Abstract: Ternary extractive distillation is a green and sustainable separation process for the treatment of pharmaceutical wastewater containing methanol/acetonitrile and acetonitrile/water azeotropes that achieves the recovery of the acetonitrile and methanol solvents. A novel sequential iterative optimization methodology is proposed and the isovolatility curves of systems at different pressures are analyzed in this work to investigate the effect of the operating pressure on the ternary extractive distillation process. Four optimization procedures with different conditions of pressure and limits for the use of cold utilities were carried out. The optimization results showed that the optimal pressures of the first column and the third column are related to the top vapor that can be condensed by chiller water and cooling water, respectively, and the pressure of the second column is related to the effect of preheating on the third column. The ternary extractive distillation process with optimal operating pressure shows 60.1% energy cost savings and 47.0% total annual cost savings compared with the optimal process operating at atmospheric pressure. The proposed optimization method has the advantages of automatic optimization with a smaller number of simulator runs, providing a new solution for the simulator-based process optimization. The investigation of the operating pressure effect provides additional insight for the design and optimization of ternary extractive distillation. Highlights: A novel sequential iterative optimization methodology is proposed. The methodology achieves optimization automatically with less computational time. The process with optimum operating pressure can achieve 60.1% energy savings. Determinants of pressures in different extractive distillation columns are different.